Circulating microRNAs Correlate with Multiple Myeloma and Skeletal Osteolytic Lesions - Sara Reis Moura (MDPI AG, 2021)
Multiple myeloma (MM) is the second most frequent hematological disease and can cause skeletal osteolytic lesions. This study aims to evaluate the expression of circulating microRNAs (miRNAs) in MM patients and to correlate those levels with clinicopathological features, including bone lesions. A panel of miRNAs associated with MM onset and progression, or with bone remodeling, was analyzed in the plasma of 82 subjects (47 MM patients; 35 healthy controls). Results show that miR-16-5p, miR-20a-5p, and miR-21-5p are differently expressed between MM patients and healthy controls. Receiver operating characteristic analyses indicate that their combined expression has potential as a molecular marker (Area Under the Curve, AUC of 0.8249). Furthermore, significant correlations were found between the analyzed miRNAs and disease stage, treatment, β2 microglobulin, serum albumin and creatinine levels, but not with calcium levels or genetic alterations. In this cohort, 65.96% of MM patients had bone lesions, the majority of which were in the vertebrae. Additionally, miR-29c-3p was decreased in patients with osteolytic lesions compared with patients without bone disease. Interestingly, circulating levels of miR-29b-3p correlated with cervical and thoracic vertebral lesions, while miR-195-5p correlated with thoracic lesions. Our findings suggest circulating miRNAs can be promising biomarkers for MM diagnosis and that their levels correlate with myeloma bone disease and osteolytic lesions.